Global image of countries in international wars: A scoping review of influencing factors - Dongyong Li; Kim Hua Tan; Jamsari Alias; Norazila Mat (PLoS ONE, 2025)
This scoping review investigates factors influencing the international or global image of countries involved in international wars. Following Arksey and O’Malley’s 5-step framework, key sources for the search include academic databases such as Google Scholar, Scopus, and Web of Science. Reporting followed the PRISMA extension for Scoping Reviews (PRISMA-ScR) (Peters et al., 2020) and was guided by the Joanna Briggs Institute (JBI) methodological guidelines. We systematically analyzed 56 peer-reviewed articles published between 2015 and 2024. Our analysis reveals that a country’s global image during war is predominantly shaped by the dynamic interplay of three core factors: (1) Historical factors, providing cognitive and affective frameworks for interpreting conflict; (2) Diplomatic factors, managing critical narrative alignment and credibility constraints; and (3) Leadership factors, embodying national resolve through symbolic representation and communicative authenticity. These factors function as interdependent pillars, where historical narratives constrain diplomatic choices, leadership enacts diplomatic narratives, and diplomacy mediates historical burdens. While secondary factors (e.g., military conduct, cultural proximity) play a role, they are largely interpreted through these core mechanisms. Additionally, the review highlights the role of emerging factors—including digital technology, affective investments, subliminal priming, diversity of information sources, and visual tropes—which represent evolving mechanisms of image formation in contemporary wars. There is a surge in research coinciding with major contemporary wars (e.g., Russo-Ukrainian War). Crucially, this interdependence underscores the necessity for integrated statecraft that strategically aligns historical reframing, diplomatic consistency, and leadership authenticity. However, the efficacy of these core factors is significantly mediated and amplified by secondary factors—such as military conduct, governmental credibility, cultural proximity, and geopolitical positioning—which collectively shape the perception and credibility of a nation’s projected image. Furthermore, emerging factorsintroduce new complexities into the image formation process, accelerating the spread and emotional resonance of narratives while also increasing scrutiny of state actions. These findings offer critical insights for policymakers, media professionals, and scholars seeking to understand and manage a nation’s global standing during and beyond conflict, moving beyond media-centric explanations of wartime perception.